Chemical Compounds Of Granulated Palm Sugar Made From Sap Of Nipa Palm (Nypa Fruticans Wurmb) Growing In Three Different Places - Rosidah R Radam; Hj. Noor Mirad Sari; Hj. Lusyani Lusyani (Journal of Wetlands Environmental Management, 2014)
Production of granulated sugar from sap of nipa palms in South Kalimantan Province is a new innovation. The purpose of this study was to find out the chemical compounds contained in granulated sugar made from sap of nipa palms growing in 3 different places, which was expected to benefit wider community as a source of alternative sweetener. The chemical compound test of granulated nipa palm sugar was conducted at the Laboratory of Institute for Research and Standardization of Industry, Banjarbaru. Chemical parameters tested were water, sucrose, reducing sugar, fat, protein, phosphorus, and potassium content. The test results showed that the water content of granulated nipa palm sugar in treatment A1, A2, and A3 was 3.69%, 4.04%, and 2.31%, respectively; the protein content 0.65%, 2.19%, and 1.10%; the fat content 0.27 %, 0.34 %, and 0.20 %; the reducing sugar content 2.39%, 0.51%, and 0.52%; the sucrose content 75.14%, 68.15%, and 88.46%; the phosphorus content 1.1342%, 1.1196%, and 1.138%; and the potassium content 1.60%, 1.40%, and 1.58%, respectively. The test parameters of granulated nipa palm sugar that met the Mandatory Indonesia National Standard (SNI) 01-3743-1995 were the water content of granulated sugar from sap of nipa palms growing in dry place (land), the reducing sugar content and sucrose content in all treatments. It can be concluded from the three required parameters that granulated nipa palm sugar is able to become the source of new sweetener in addition to block arenga palm sugar and crystal cane sugar for the community in South Kalimantan.